2019
DOI: 10.5897/jmpr2018.6680
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of antioxidant and antidiabetic properties of Picralima nitida seed extracts

Abstract: The study investigated the antioxidant potential as well as the inhibitory potential of the seed extracts of Picralima nitida on α-amylase and α-glucosidase enzymes. The methanolic, aqueous and coconut water extracts were obtained using 70% methanol, distilled water and coconut water, respectively. Antioxidant properties were studied in vitro using DPPH (1, 1-diphenyl-2-pricrylhydrazyl) radical scavenging, Ferric Reducing Antioxidant Power (FRAP), Total Antioxidant Capacity (TAC), Hydroxyl Radical Averting Cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that various extracts of the plant are good sources of these compounds. 6,7,40,41 The result obtained from the study also showed that APN could scavenge DPPH. The ascorbic acid, however, was able to scavenge DPPH more effectively than APN.…”
Section: Resultsmentioning
confidence: 71%
“…Previous studies have shown that various extracts of the plant are good sources of these compounds. 6,7,40,41 The result obtained from the study also showed that APN could scavenge DPPH. The ascorbic acid, however, was able to scavenge DPPH more effectively than APN.…”
Section: Resultsmentioning
confidence: 71%
“…The differences between our work and previous studies may be due to the type of extraction solvent used because some of the previous studies used solvents and not water. For example, the TPC of picralima seed from aqueous extraction was reported to be 435.87 ± 1.76 mg GAE/g, whereas it was 356.53 ± 4.67 mg GAE/g for the methanol extract (Akinwunmi & Amadi, 2019). Similarly, the TPC content of date plum water extract was 14.5 ± 0.20 mg GAE/g when compared to 1.6 ± 0.12 mg GAE/g for the acetone extract (Gao et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Leaves were the most used part. Many previous studies showed the use of leaves in the preparation of various recipes in traditional medicine (Akinwunmi and Amadi, 2019;Zahoor et al, 2017;Odewo and Adeyemo, 2018;Balcha, 2014).…”
Section: Discussionmentioning
confidence: 99%